Libertades coreografiadas: palabras habladas, comunicaciones corporales y códigos en pistas dance de la ciudad de Buenos Aires - Gallo, Guadalupe M. (El Colegio de México, 2016)
Native references and academic literature agree to characterize the production and appreciation of dance music as an aesthetic phenomenon aimed at building dance music events characterized by freedom, liberation, expression, social inclusion and tolerance. Raves, clubs, parties and electronic festivals dance are valued for djs and dancers to be social gatherings constructed from synergy between musical practice and dance practices not choreographed since in these dance floors participants and the technologies involved (lights, music, drugs, digital technologies) are articulated, merge and involve each other. Thus, in these contexts, plural practices and different dance are enabled as effective and communicative hands off instances of the word spoken between musicians and audiences. From an ethnographic description that characterizes the dance floor and problematizes the relationship between spoken word and movement in these social and musical contexts, this paper analyzes and interrogates constructions of meaning around these practices dance patterns absent practices and evaluations choreographic to discuss the modalities of processing the difference, heterogeneity and individuals of this socio-aesthetic phenomenon social exclusion.